2012
DOI: 10.1002/lary.23420
|View full text |Cite
|
Sign up to set email alerts
|

Middle ear myoclonus associated with forced eyelid closure in children: Diagnosis and treatment outcome

Abstract: FECS is a rare clinical entity and can be easily missed in routine clinical examination. We suggest that patients, especially children, with clicking or crackling tinnitus should be evaluated for FECS using proper diagnostic tools. A possible mechanism of FECS in children postulated from our case review is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 11 publications
0
23
1
Order By: Relevance
“…Tinnitus secondary to middle ear myoclonus is very rare, and consequently there are very few reports of it in the English literature [8][9][10][11][12]. It has been suggested that the crackling or buzzing sounds reported are caused by repetitive and abnormal tensor tympani and stapedial muscles contractions [11].…”
Section: ) Etiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Tinnitus secondary to middle ear myoclonus is very rare, and consequently there are very few reports of it in the English literature [8][9][10][11][12]. It has been suggested that the crackling or buzzing sounds reported are caused by repetitive and abnormal tensor tympani and stapedial muscles contractions [11].…”
Section: ) Etiologymentioning
confidence: 99%
“…It has been suggested that the crackling or buzzing sounds reported are caused by repetitive and abnormal tensor tympani and stapedial muscles contractions [11]. These myoclonic movements are thought to be a form of segmental myoclonus involving brainstem innervated muscles.…”
Section: ) Etiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Forced eyelid closure syndrome (FECS) is an exceedingly rare form of objective tinnitus, with only 11 cases reported in the literature since 1983 . Objective tinnitus is often associated with underlying pathologies such as myogenic dysfunction, vascular abnormalities, temporomandibular joint disease, and patulous Eustachian tube dysfunction .…”
Section: Introductionmentioning
confidence: 99%
“…Objective tinnitus is often associated with underlying pathologies such as myogenic dysfunction, vascular abnormalities, temporomandibular joint disease, and patulous Eustachian tube dysfunction . Myogenic objective tinnitus is thought to result from abnormal contractions of the palatal and middle ear muscles, namely the tensor veli palatini, stapedius, and/or tensor tympani muscles . Palatal tremor and middle ear myoclonus (palatal tinnitus) are more common causes of myogenic objective tinnitus but lack the involvement of the periorbital muscles seen in FECS .…”
Section: Introductionmentioning
confidence: 99%